Water quality assessment in Réghaïa (North of Algeria) lake basin by using traditional approach and water quality indices - Bouhezila, Farouk; Hacene, Hocine; Aichouni, Mohamed (Kuwait Journal of Science, 2020)
Réghaïa town, located in Algiers (North of Algeria), presents a strong anthropogenic activity. The aim of this study is to assess water quality in Réghaïa lake basin by determining current status, temporal evolution and apportionment of pollution sources. Three samplings were carried out in fourteen stations covering the lake and its principal tributaries. Sixteen physical-chemical parameters and three microbiological parameters were analyzed. Surface Water Quality Evaluation System (SW-QES) was used to visualize the temporal evolution of available data from 1978 to 2017. Water quality index (WQI) was used to assess the global water quality for irrigation purpose and its spatial variation across the basin. Organization for Economic Co-Operation and Development (OECD) international classification and trophic state index (TSI) were used to evaluate trophic category of the lake. Organic pollution index (OPI) and microbiological quality index (MQI) were used to establish pollution maps of the study area. The lake presents excessive pollution since the 1970s. BOD5/COD ratio (0.1) recorded in 2017 indicates a very low biodegradability of Réghaïa lake waters. The value of Canadian Council of Ministers of the Environment-water quality index (CCME-WQI) (14.31) indicates poor water quality. The values of Weighted arithmetic-water quality index (WA-WQI) are extremely high (>4000) which indicates unsuitable water quality for irrigation purpose. Hypertrophic nature of the Réghaïa lake was identified (TSI > 80) and confirmed by the OECD classification. Spatial distribution of pollution indicators shows that Réghaïa river and ElBiar river are the most important pollution sources. Calculations of WA-WQI with and without Coliforms indicate that Réghaïa river is the most important microbial pollution source. A slight decrease in organic pollution and remarkable improvement in microbiological quality was observed at the outlet of the lake. According to these results, sewage discharged without or with insufficient treatment is the main pollution source of the Réghaïa lake which has been a receiving environment for many years and continues to be polluted today and tomorrow If we do not react effectively by stopping the pollution sources.